2020
DOI: 10.1002/ajb2.1542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought and carbon dioxide on nutrient uptake and levels of nutrient‐uptake proteins in roots of barley

Abstract: Atmospheric carbon dioxide (CO 2) concentration is increasing, as is the frequency and duration of drought in some regions. Elevated CO 2 can decrease the effects of drought by further decreasing stomatal opening and, hence, water loss from leaves. Both elevated CO 2 and drought typically decrease plant nutrient concentration, but their interactive effects on nutrient status and uptake are little studied. We investigated whether elevated CO 2 helps negate the decrease in plant nutrient status during drought by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 59 publications
(100 reference statements)
0
8
1
Order By: Relevance
“…We also found that the early-stage drought stress decreased biomass at 700 ppm CO 2 level. It was found that under elevated CO 2 (700 ppm) water limitation at the terminal growing stage reduced biomass in durum wheat, according to Garmendia et al [51], and in barley, according to Bista et al [52]; however, in the case of the examined barley cultivar, we found increased biomass values compared to the control. In disagreement with our findings, Varga et al [28] found no significant differences in the plants' biomass between the well-watered and drought-stressed winter wheat at different developmental stages at elevated CO 2 level (1000 ppm), which fact confirms the variety-specific CO 2 responses.…”
Section: Discussioncontrasting
confidence: 55%
“…We also found that the early-stage drought stress decreased biomass at 700 ppm CO 2 level. It was found that under elevated CO 2 (700 ppm) water limitation at the terminal growing stage reduced biomass in durum wheat, according to Garmendia et al [51], and in barley, according to Bista et al [52]; however, in the case of the examined barley cultivar, we found increased biomass values compared to the control. In disagreement with our findings, Varga et al [28] found no significant differences in the plants' biomass between the well-watered and drought-stressed winter wheat at different developmental stages at elevated CO 2 level (1000 ppm), which fact confirms the variety-specific CO 2 responses.…”
Section: Discussioncontrasting
confidence: 55%
“…58 In this study, drought significantly reduced the accumulation of plant N, P and K by the end-of-drought harvest in all sorghum species, suggesting that the forage quality of these drought-stressed plants also decreased. It has been recognized for decades that drought can decrease the rate of nutrient uptake by plants, independent of water uptake, 59,60 and hamper uptake and transference of macronutrients (N, P and K) in many plant species. [61][62][63] Nitrogen fertilization increased the content of N, P and K in all sorghum species under both well-watered and drought-stressed conditions, particularly at 120 kg N ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…In barley, drought stress alone significantly reduces the uptake of N and P but the increase of CO 2 has no clear effect. However, high levels of CO 2 and drought cause a mild increase in the activity of NRT1 and AMT1 which are root transporters for NO 3 − and NH 4 + , respectively (Bista et al, 2020). This observation could indicate a positive effect in the uptake of nutrients under drought stress caused by elevated CO 2 .…”
Section: Environmental and Atmospheric-related Stressesmentioning
confidence: 98%
“…Thus, elevated CO 2 has been correlated with enhanced root biomass, length, area and density due to an increase in carbon assimilation in sorghum (Chaudhuri et al, 1986). An increase in root length, as a consequence of elevated CO 2 and drought, has been observed in several crops such as wheat, barley and coffee (Chaudhuri et al, 1990;De Souza et al, 2015;Avila et al, 2020;Bista et al, 2020). In addition to the effect on root growth, elevated CO 2 also enhances root respiration in drought-stressed pepper plants (del Amor et al, 2010).…”
Section: Environmental and Atmospheric-related Stressesmentioning
confidence: 99%